Pembudayaan Nilai-Nilai Luhur Pancasila Melalui Pendidikan Kewarganegaraan - Sulistyanto . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2013)
Writing this paper aims to determine how institutionalized the noble values of Pancasila through civic education. Writing method using library research. From the results of the discussion can be concluded that the values of Pancasila acculturation among young citizens can now be done through the educational process. Proper education is the education of Pancasila which can be done by Citizenship Education. However, since the charge material Pancasila in Civics yet cover the whole of Pancasila as the basic competencies and idologi nations, the Pancasila as appropriate by education subjects / courses devoted to Pancasila in learning right through subjects / courses in special education Pancasila.